Islamic Character Education Development Strategy Shaping Students Spiritual Intelligence at SD Islam Al Hidayah Sragen - Tri Wibowo; Muna Yastuti Madrah; Choeroni Choeroni (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Education plays a pivotal role in shaping a generation that excels not only academically but also in character and spiritual intelligence. This study aims to explore the strategies for developing Islamic character-based education at SD Islam Al Hidayah Sragen to enhance students spiritual intelligence. Using a qualitative descriptive method, data were gathered through observations, interviews, and documentation, then analyzed using triangulation techniques to ensure validity. The findings reveal that development strategies are implemented through the systematic integration of Islamic values into daily activities, including congregational Dhuha prayers, Quran memorization, and the 5S program. A distinctive novelty in this study is the holistic synergy between schools and parents through home-activity monitoring instruments, alongside the installation of practical muamalah ethics via Market Day events. Consequently, these programmed habits significantly strengthen students faith (aqidah), Sharia, and morality (akhlaq) in an integrative manner. The study concludes that active stakeholder collaboration is the key to fostering resilient spiritual intelligence as a vital filter against globalization challenges and digital disruption.